Detailed Analysis of the UCMR 3 Database: Implications for Future Groundwater Monitoring. Issue 4 (9th April 2018) - Eaton, Andrew; Bartrand, Tim; Rosen, Saul
Abstract : Under the Safe Drinking Water Act, the US Environmental Protection Agency requires monitoring every five years for up to 30 unregulated contaminants under the Unregulated Contaminant Monitoring Rule (UCMR). Results include analyte concentrations and additional metadata. The third iteration of the UCMR (UCMR 3) is as unique as the first, with a variety of detection frequencies, from <0.1% to nearly 100%. Groundwater systems are required to sample twice, five to seven months apart. A detailed analysis of results for groundwater systems in UCMR 3 demonstrates that other than for chlorate, a disinfection byproduct, there is no significant difference in either concentrations or overall occurrence frequency between the two events. For future UCMRs, depending on the selected contaminants, a single sample would generate the same information for overall distributions, even if individual locations might have differences between events. There are differences in occurrence as a function of population for most contaminants. Either fewer sample events and/or stratified sampling could save utilities as much as 10–20 million over the course of the UCMR three‐year monitoring period without changing the overall conclusions regarding occurrence frequency.